Association between Different Types of Edible Oils and Anthropometric Indices Mood, and Appetite among Women. (19th October 2022) - Kangani, Nahid; Mohammadi, Mohammadreza; Zeinolabedin, Mobina; Bellissimo, Nick; Azadbakht, Leila
Abstract : Introduction . The objective of this study was to evaluate the relationship between consumption of dietary oils and anthropometric indices, mood, and appetite among women staff of Tehran University of Medical Sciences. Methods . A cross-sectional study design was used, and 245 women staff of Tehran University of Medical Sciences participated. A 168-item food frequency questionnaire was used to evaluate dietary and nutrient intake. The association between liquid vegetable oils, hydrogenated vegetable oil, and animal fat intake and anthropometric indices, appetite, and mood was evaluated. The Profile of Mood States (POMS) questionnaire was used to assess mood. A Visual Analogue Scale (VAS) was used to evaluate appetite status. The tape measure was used to measure the waist circumference and height. SPSS was used to compute body mass index (BMI) and waist-to-height ratio (WHtR). Results . In the present study, sunflower and frying oil were the most consumed liquid oils ( n = 135/245 participants). Participants with a moderate intake of MUFA had greater odds ratio (OR: 3.47; 95% CI: 1.20–10.7; P trend = 0.025) of a high appetite compared to those with a low intake of MUFA. However, the study found no evidence of an association between consumption of edible oils (vegetable oils, animal fat oils, and other fatty acid sources) and mood, anthropometric indices, or appetite. Conclusions . In the current research, we noticed a significant connection between moderate intake of MUFA and a large appetite and no association between consumption of edible oils and other outcomes. In conclusion, a balanced diet low in fast meals, processed foods, cakes, cookies, and sweets is suggested to limit the consumption of artificial trans-fatty acids.